2017
DOI: 10.1002/jbm.a.36123
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctiva derived mesenchymal stem cell (CJMSCs) as a potential platform for differentiation into corneal epithelial cells on bioengineered electrospun scaffolds

Abstract: With the aid of tissue engineering, the capability of nanofibrous scaffolds was examined for corneal epithelial differentiation of Conjunctiva mesenchymal stem cells (CJMSCs) as a new source. This study tried to provide a synthetic corneal sheet which could be applied in corneal regeneration. The hybrid arrangement of fine Silk fibers with the diameter of 93.65 nm and the polyurethane (PU) fibers with an average diameter of 575.5 makes a mat with sufficient mechanical properties and interconnected pores that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The final goal of this study was the differentiation of the CJMSCs as a new source of stem cells to neuron‐like cells. One of the most priorities of CJMSCs in comparison with other adult stem cells is their ectoderm origin, so there is no need to use the complicated and expensive reprogramming process 72 . The NT‐3, the neurotrophin family's growth factor, is a key factor in neuron viability and axonal growth during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…The final goal of this study was the differentiation of the CJMSCs as a new source of stem cells to neuron‐like cells. One of the most priorities of CJMSCs in comparison with other adult stem cells is their ectoderm origin, so there is no need to use the complicated and expensive reprogramming process 72 . The NT‐3, the neurotrophin family's growth factor, is a key factor in neuron viability and axonal growth during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…21 In another study, Soleimanifar et al reported the differentiation of conjunctival MSC into corneal epithelial cells. 22 Hence it is an established concept that limbus derived cells are capable of transdifferentiating MSCs. In this study, four potential markers related to trans differentiation of BMSCs like CK3, CK12, ABCG2 and P63 were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Silk fibroin, a natural protein extracted from Bombyx mori cocoons, can be formed into films and scaffolds with tunable degradation and mechanical strength with non-immunogenic responses in vivo [ 38 , 80 , 81 ]. Use of silk fibroin as a film or scaffolds for corneal tissue replacement [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] remains an active area of research, as outlined in Table 3 . Silk films and membranes can be fabricated through simple evaporation or electrospinning.…”
Section: Engineering a Cornea Mimetic: Mechanical Properties And Biomaterials Structurementioning
confidence: 99%